Description of Pregnant Women Using Maternal and Child Health (MCH) Books as Information Media - Ayu Endang Purwati; Rosidah Solihah; Aulia Ridla Fauzi; Kartika Ayu (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2023)
Introduction: During pregnancy, the mother will experience various physical and psychological changes. Fulfillment of psychological needs is obtained from health information and education, supported by interesting information media. The MCH handbook is very important for mothers to own and understand in order to make it easier to monitor the health of mothers and children. Objective: This study aims to describe pregnant women who use the MCH Handbook as an Information Media in the Sumberjaya Poskesdes Working Area in 2022. Method: This research is a quantitative research with a quantitative descriptive research design. The sample in this study were all pregnant women who came to the Poskesdes to do an examination and have a MCH handbook. Retrieval of data using a total sample technique, namely 40 respondents. Retrieval of data using primary data in the form of a questionnaire. The research was conducted from November-December 2022. Result: The majority of pregnant women aged 20-35 years (85%) had used the MCH Handbook as much as 52.9% as a medium of information. The majority of respondents had low education (70%) with 57.2% had not used the MCH handbook as an information medium. Most of the respondents belong to the second trimester category (55%) and 54.5% have used the MCH Handbook as a medium of information. The majority of respondents are housewives who do not work (65.5%) and the majority have used the MCH handbook as a medium of information as much as 51.6%. The majority of pregnant women did not use the MCH Handbook as Information Media as much as 52% with the majority having sufficient knowledge. Conclusion: Most of the respondents have used the MCH Handbook as an Information Media apart from being a notebook for monitoring Maternal and Child Health.